1998
DOI: 10.1007/pl00005257
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of α1-adrenoceptor subtypes in the rabbit spleen

Abstract: Phenylephrine and (+/-)N-[5-(4,5-dihydro-1-H-imidazol-2yl)-2-hydroxy-5,6,7,8-tetr ahydronaphthalen-1-yl] methanesulphonamide hydrobromide (A 61603) evoked concentration-dependent contractions of the rabbit spleen. These contractions were antagonized by prazosin (10(-8)-10(-7) M) with pA2 values of 8.34+/-0.11 and 8.15+/-0.10 against phenylephrine and A 61603, respectively. In both cases, the slopes of the Schild plots were not significantly (P>0.05) different from 1.0, indicating competitive antagonism. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In laboratory rodents, however, extremely few smooth muscle cells are found in the capsule (Tischendorf, 1968;Kai, Nishizono and Kimura, 2000) and elastic fibers are more highly developed than the musculature (Gross, 1951;Tischendorf, 1968). A strong contraction of the spleen in rodents has also been reported in pharmacological experiments in the rat (Aboud, Schhaffi and Docherty, 1993; Burt et a!., 1995; Stam, V. Graaf and Saxena, 1998), mouse (Eltze, 1996), and rabbit (Oriowo, 1998) which is considered to be due to a large amount of smooth muscle cells.…”
mentioning
confidence: 65%
“…In laboratory rodents, however, extremely few smooth muscle cells are found in the capsule (Tischendorf, 1968;Kai, Nishizono and Kimura, 2000) and elastic fibers are more highly developed than the musculature (Gross, 1951;Tischendorf, 1968). A strong contraction of the spleen in rodents has also been reported in pharmacological experiments in the rat (Aboud, Schhaffi and Docherty, 1993; Burt et a!., 1995; Stam, V. Graaf and Saxena, 1998), mouse (Eltze, 1996), and rabbit (Oriowo, 1998) which is considered to be due to a large amount of smooth muscle cells.…”
mentioning
confidence: 65%
“…The contractility of the spleen has been used as a model to identify α1 receptor subtypes and to test the efficacy of α1 receptor antagonists, such as prazosin (Aboud et al, 1993, Oriowo, 1998, Bolognesi et al, 2001). Other groups have suggested that the decrease in spleen size following experimental stroke is due to profound apoptosis of the lymphocyte population in the spleen (Offner et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%